Obtenção de parâmetros de resistência e verificação da estabilidade de talude de um solo da cidade de Cruz Alta/RS - Rodrigues, Juliana Bezerra (2019)
This study seeks to evaluate the stability of the road slope of the northern access work via RS 342 to the city of Cruz Alta, central-north of the state of Rio Grande do Sul. The construction work consists of a 14.20 m slope of landfill embankment in soil of 1.0V: 1.5H, with 95% spreading and compaction. The ground used, located in the coordinates 28º37'39.40 "south and 53º37'30.50" west, presents three distinct horizons, and the C horizon was used to compose the body of the landfill, object of study of this work. After determination of the optimal humidity and density for the normal and intermediate energies, direct shear tests were performed from laboratory compacted samples in both energies, tested in the optimal humidity and in the flooded condition. Also, they were extracted with undisturbed samples that were tested in the natural humidity and in the flooded condition. With the friction angle and soil cohesion data, it was possible to simulate the slope of the work with the aid of computational software. The slope was analyzed for stability using Bishop Simplified, Janbu Simplified and Janbu Corrected methods